The effect of a water-soluble β-glucan on intestinal immunity and microbiota in LPS-challenged piglets - Wu, Yuliang; Li, Yuxin; Chen, Mengli; Zhao, Juan; Xiong, Xia; Olnood, Chen Guang; Gao, Yundi; Wang, Fei; Peng, Can; Liu, Miao; Huang, Chunxia; Li, Jianzhong; et al. (Frontiers in Veterinary Science, 2025)
The intestine is the largest immune and barrier organ in the body, and diarrhea and even death during piglet development are related to dysfunction caused by intestinal barrier damage and inflammation. A water-soluble β-glucan produced by Agrobacterium ZX09 has been shown to have a beneficial effect on gastrointestinal health. The main objective of this study was to investigate whether pre-feeding β-glucan has a protective effect on LPS-induced immune stress in piglets. In this study, 24 weaned piglets (21-day-old; 6.64 ± 0.16 kg) were assigned to 4 treatments in a two × two factorial design with diet (with or without β-glucan) and immunological challenge (saline or LPS). Piglets were challenged with saline or LPS after 39 days of feeding 0 or 200 mg/kg β-glucan. The results demonstrated that β-glucan supplementation increased the average daily weight gain and daily feed intake, and decreased diarrhea rate of piglets. Intestinal inflammation symptoms and histological changes in LPS-challenged piglets were alleviated by pre-feeding of β-glucan. β-glucan supplementation reduced serum IL-1β (interleukin-1β) and NO (nitric oxide) secretion in piglets after LPS challenge (0.01 < p < 0.05). Supplementation with β-glucan downregulated the mRNA expression of IL-6 in piglets after LPS challenge (0.01 < p < 0.05). β-glucan supplementation enriched the short-chain fatty acid-producing bacteria, such as Agathobacter and Subdoligranulum (0.01 < p < 0.05), and increased the concentrations of propionate and butyrate (0.01 < p < 0.05). In conclusion, pre-feeding β-glucan can enhance piglet immunity and promote piglet growth by influencing gut microbiota composition and metabolism, and alleviate intestinal damage after LPS challenge.